Instruments for wound assessment: scoping review (Research, Society and Development, 2021)
The aim is to identify and describe the main instruments used for wound analysis, in addition to raising their validation and cross-cultural adaptation to the Portuguese language. This is a scope review prepared according to the method proposed by the Joanna Briggs Institute. The Regional Portal of the Virtual Health Library (BVS), MEDLINE (under the Pubmed interface), Scopus, Web of Science, CINAHL, LILACS and Scielo databases were consulted in order to identify studies that used at least one instrument validated for wound assessment by January 2021. Gray literature was verified using Google Scholar. The search strategy was developed using Health Science Descriptors (DeCS) and MeSH terms such as wound healing, assessment study and nursing assessment. Studies were included regardless of the design used, only studies that did not report the use of any instrument for wound assessment, or studies involving preclinical models were excluded. Two reviewers selected the articles independently. The instruments found were described and categorized after the reviewers' calibration. 51 instruments for wound assessment were found in a total of 110 selected studies. These instruments involved different approaches in clinical practice (wound healing, infection, pain caused by the wound, etc.). However, only eight (15.7%) were cross-culturally adapted for use in the Portuguese language. This study suggests that more instruments must be developed and adapted to the Portuguese language of Brazil, so that the diagnosis and treatment of wounds can be more accurate.